2012
DOI: 10.1103/physrevlett.108.227002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Spin Resonance Mode in the Iron-Based SuperconductorBa0.6K0.4Fe2As2from Scanning Tunneling Spectroscopy

Abstract: We used high-resolution scanning tunneling spectroscopy to study the hole-doped iron pnictide superconductor Ba(0.6)K(0.4)Fe(2)As(2) (T(c)=38 K). Features of a bosonic excitation (mode) are observed in the measured quasiparticle density of states. The bosonic features are intimately associated with the superconducting order parameter and have a mode energy of ~14 meV, similar to the spin resonance measured by inelastic neutron scattering. These results indicate a strong electron-spin excitation coupling in iro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 48 publications
12
67
0
Order By: Relevance
“…In Nd-1111, the Eliashberg function extracted from d 2 I(V)/dV 2 [14] well matches the calculated one, and the phonon density of states [44]. Scanning tunneling spectroscopy (STS) studies with Ba 0.6 K 0.4 Fe 2 As 2 revealed a fine structure attributed to a coupling of quasiparticles with a bosonic mode near 14 meV [43]. In contrast, in STS probe with SmFeAsO 1−x F x [42], the minimum of the dip-hump structure was attributed to a sign of a resonance spin mode within the energy range ε res = 2 − 8 meV.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In Nd-1111, the Eliashberg function extracted from d 2 I(V)/dV 2 [14] well matches the calculated one, and the phonon density of states [44]. Scanning tunneling spectroscopy (STS) studies with Ba 0.6 K 0.4 Fe 2 As 2 revealed a fine structure attributed to a coupling of quasiparticles with a bosonic mode near 14 meV [43]. In contrast, in STS probe with SmFeAsO 1−x F x [42], the minimum of the dip-hump structure was attributed to a sign of a resonance spin mode within the energy range ε res = 2 − 8 meV.…”
mentioning
confidence: 72%
“…More recent theoretical studies showed that in framework of both s ++ and s ± models the dynamic spin susceptibility has a feature near ∆ L + ∆ S energy, a sharp peak related to spin resonance in s ± state, or spectral density enhancement above ∆ L + ∆ S in s ++ state [25,32]. Tunneling contact probes could provide information about electron-boson interaction [33][34][35][36][37][38][39][40][41][42][43]. For tunneling normal metal -insulator -superconductor (NIS) junction, the derivative d 2 I/dV 2 of dynamic conductance spectrum at bias voltages V > ∆/e represents a spectral function of electron-boson interaction [41].…”
mentioning
confidence: 99%
“…More recently, the method has been also applied to (Li 1−x Fe x )OHFe 1−y Zn y Se with only electron Fermi surface pockets 74 . For the 122 doped systems, such an experiment has not been yet performed; however, one would expect that such a test is feasible in these compounds as well, given the availability of the high-quality STM data 75,76 . Here we show that the QPI patterns contain information on the phase difference between the order parameters of different bands for the case when it is not 0 or π and even if one of the bands is incipient.…”
Section: Stm-signatures Of S + Is-statementioning
confidence: 99%
“…While evidence that self-energy effects due to electron-boson-coupling phenomena are occurring in iron-based materials abounds [26][27][28][29][30][31][32] , a direct comparison between a theoretical prediction with realistic band/gap structure that distinguishes effects of coupling to AFSF from those due to coupling to E g -phonons generating the orbital fluctuations, has not been achieved. Here, by combining new theoretical insight into QPI discrimination between Σ(k,ω) from resonant-AFSF and Σ(k,ω) due to alternative scenarios, together with novel QPI techniques designed to visualize the Σ(k,ω)…”
mentioning
confidence: 99%